Enhancing essential amino acid bioavailability of soy protein through Streptococcus thermophilus ST4 supplementation - Wibisono, David Agus Setiawan; Saw, Chiou-Yeong; Jian, Bo-Long; Lau, Der-Kai; Chen, Wei-Jen; Chu, Hui-Fang; Liu, Cheng-Yen; Chau, Chi-Fai (Frontiers in Microbiology, 2026)
BackgroundSoy protein is a popular plant-based protein source, but is nutritionally limited by its incomplete essential amino acid profile and lower bioavailability relative to animal proteins. Emerging evidence suggests that probiotics may improve the absorption of amino acids from plant proteins.MethodsOur research evaluated the ability of Streptococcus thermophilus ST4 to improve the soy protein nutritional quality by increasing the bioavailability of essential amino acids, using in vitro digestion models, as well as animal experiments.ResultsAfter 4 h, supplementation with S. thermophilus ST4 increased amino acid concentrations in vitro. Total amino acids rose by up to 96.9%, essential amino acids by 69.1%, and non-essential amino acids by 124.4%. Afterward, rats fed either a standard or high-protein diet received S. thermophilus ST4 at doses of 1 × 107 or 1 × 109 CFU/day. High-dose treatment significantly elevated serum total amino acids by 29.7–32.4% and essential amino acids by 37.7–43.2% (p < 0.01). Postprandial analysis further confirmed a 62.0% increase in essential amino acids in the high-protein group following probiotic supplementation.ConclusionS. thermophilus ST4 supplementation improved the nutritional quality of soy protein by enhancing essential amino acid bioavailability. These findings support its application as a probiotic for improving plant-based protein utilization, offering a practical dietary strategy to address amino acid limitations in vegetarian and high-protein diets.